Hydatid cyst of the uterus. - Başgül, A (2002)
BACKGROUND: Hydatidosis is a common zoonosis that affects a large number of humans and animals, especially in poorly developed countries. The infesting parasite has four forms named Echinococcus granulosis, E. multilocularis, E. vogeli and E. oligarthrus (very rare in humans). The most frequently involved organs are liver followed by the lung. The involvement of the genital tract is rare and the occurrence in the uterus is an extreme rarity. We report a case of hydatid cyst in the uterus. CASE: A 70-year-old female with a history of hydatid cysts of the liver, was admitted to hospital after complaining of low abdominal pains. On physical and gynecological examinations, no pathological finding was detected. However, the uterus was significantly large for a postmenopausal patient. Transvaginal sonography (TS) revealed a cystic mass in the uterus with a size of 7 x 6 cm. After further examinations a subtotal hysterectomy was performed. Microscopic examination showed scolices of Echinococcus granulosis. CONCLUSION: Hydatid cysts in the genital tract are rare and the occurrence in the uterus is an extreme rarity. Differentiation between hydatid cyst and malignant disease of the related organ is difficult. To avoid misdiagnosis, a careful examination of pelvic masses should be carried out in endemic areas for detection of hydatid cysts.